2021
DOI: 10.1007/s40891-021-00327-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microbially Induced Calcite Precipitation for Soil Improvement in Compacted Clays

Abstract: In line with the recent promotion of biocementation as an environmentally friendly ground improvement method, this study presents an investigation into microbially induced calcite precipitation (MICP) as a method of improving the engineering properties of soft clay. Bacillus pasteurii bacterium in vegetative cell and bacterial spore forms were used to induce MICP in clay specimens. Untreated and treated clay specimens were tested for their mechanical properties and microstructures through unconfined compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…This is consistent with recent research, which found that the coefficient of permeability of MICCP treated sand reduces nonlinearly as the CaCO 3 level rises [17]. To assist the MICCP process in geo-technical engineering practices, a large scale analysis of MICCP applications are recommended [18]. In general, the outcome proved the capability of bio-cementation to amend considerably the different features of the sandy soil, even for a minor amount of cementation; this is used asan alternative for accessing the settlement property of this sandy soil [19].…”
Section: Introductionsupporting
confidence: 85%
“…This is consistent with recent research, which found that the coefficient of permeability of MICCP treated sand reduces nonlinearly as the CaCO 3 level rises [17]. To assist the MICCP process in geo-technical engineering practices, a large scale analysis of MICCP applications are recommended [18]. In general, the outcome proved the capability of bio-cementation to amend considerably the different features of the sandy soil, even for a minor amount of cementation; this is used asan alternative for accessing the settlement property of this sandy soil [19].…”
Section: Introductionsupporting
confidence: 85%
“…Soil-strengthening technologies can be used in ground improvement [1,2]. The stabilization methods used can be divided into chemical, mechanical, or chemical-mechanical stabilization [3].…”
Section: Introductionmentioning
confidence: 99%
“…of applications such as concrete remediation, wind erosion prevention, and landform stabilization (Arpajirakul et al 2021;Bayat et al 2021;Pungrasmi et al 2019). The precipitation of CaCO 3 crystals on the surface of sediment facilitates binding at the contact points between tailings particles and reduces the size of the pore spaces, which can improve the mechanical strength of the soil matrix and reduce permeability (Gui, et al 2018;Harkes et al 2010;Punnoi et al 2021). This treatment could be advantageous for tailings attenuation, as the formation of a cemented "biocrust" in the upper layer of tailings would reduce water and oxygen ingress, thus limiting the exposure of stored tailings to the weathering processes that control ARD.…”
Section: Introductionmentioning
confidence: 99%